Pengaruh Digital Marketing, dan Harga Terhadap Kepuasan Konsumen pada EOS Galeri Kecamatan Peusangan Kabupaten Bireuen - Firmansyah, Firmansyah; Nuraisa, Rizka (Aceh Cooperative Care, 2025)
Digital media is increasingly popular for shopping, thanks to advances in e-Business and e-Commerce technology. The level of satisfaction with digital media marketing still varies, alongside factors such as price, quality, and service. This study analyzes consumer satisfaction based on the availability of digital media and the price of goods. Quantitative research was conducted using multiple regression analysis. The study was conducted at EOS Gallery in Peusangan, Bireuen Regency. The results showed that: (1) digital marketing has a significant influence on consumer satisfaction. (2) Price has also been shown to have a significant influence on consumer satisfaction. (3) Simultaneously, digital marketing and price have a positive contribution to increasing consumer satisfaction, although small, at around 10.5%. Digital marketing has a higher influence than price on consumer satisfaction at EOS Gallery in Peusangan District, Bireuen Regency